Evaluating adherence in an active-controlled HIV pre-exposure prophylaxis trial (PrEPVacc) to inform the estimation of HIV incidence in a counterfactual placebo arm - Sheila Kansiime; Christian Holm Hansen; Henry Bern; Julie Fox; David Dunn; Eugene Ruzagira; Richard Hayes; Sheena Mc Cormack; on behalf of the PrEPVacc study team (HIV Research & Clinical Practice)
Background Inferring the counterfactual placebo HIV incidence using the estimated effectiveness of Emtricitabine/Tenofovir (TDF/FTC) in active-controlled pre-exposure prophylaxis (PrEP) trials has been suggested. However, it has not yet been widely applied. In this article, we evaluate adherence to TDF/FTC in the PrEPVacc trial (NCT04066881) and consider how such adherence data could be used to estimate the effectiveness of TDF/FTC and subsequently, HIV incidence in a counterfactual placebo arm in a predominantly female population. Methods From December 2020 to March 2023 participants were recruited into the trial which included a comparison of Emtricitabine/Tenofovir Alafenamide (TAF/FTC) to TDF/FTC as PrEP over 26 weeks of follow-up, in Uganda, Tanzania, and South Africa. PrEP adherence was assessed in various ways. Results Of 697 participants dispensed TDF/FTC, 87% were female, 54% were ≥ 25 years, and 59% were sex workers. In a random sample (41%) assessed at visit 6 (week 8), 76% had detectable TFV-DP levels, with 22% reaching levels consistent with ≥2 pills/week. Males, Verulam and Mbeya participants, those ≥ 25 years, not single, subsistence fisheries workers, and those who had any STI at baseline were more likely to have higher adherence. Of those assessed at visit 6, 29% were identified as white coat dosing. Estimated (crude) HIV incidence risk reduction ranged from 10% to 65%. Conclusions TDF/FTC adherence in the PrEPVacc trial was low, with considerable levels of white coat dosing. Inferring the counterfactual placebo HIV incidence using the estimated effectiveness of TDF/FTC is a promising approach, however, the approach requires further elaboration and evaluation.